Challenges of parallel ESS cryoplants installation and commissioning activities. (April 2019) - Arnold, P; Gous, H; Phan, D; Su, Xiaotao; Weisend, J G II
Abstract: The European Spallation Source (ESS) is a neutron-scattering facility being built with extensive international collaboration in Lund, Sweden. The world's most powerful linear proton accelerator shoots protons against a rotating tungsten target where neutrons are knocked off ("spallate") and are guided to the neutron instrument suites [1]. Three cryogenic plants and a vast cryogenic distribution system serve the cooling needs of the superconducting RF cavities in the accelerator, the cold hydrogen moderators in the target, a cryomodule test stand and the sample environments for neutron instruments. The project's demand of schedule and economic feasibility requires a high degree of parallel work for installation and commissioning of the cryogenic and auxiliary systems. The resulting challenges in aspects such as safety, interface control, utility management and planning for the phases of installation and pre-commissioning shall be discussed in this paper. The current status of the ESS cryogenic system and lessons learned are addressed as well.